The importance of scheduling towards an efficient public transport integration: feeder bus and Light Rail Transit (LRT) / Salmah Ibrahim - Ibrahim, Salmah (1995)
LRT system need a dedicated feeder bus system for the commuters to access and egress from an LRT2 station on time. As to give efficient and effective service to the public scheduling between LT and feeder bus is important. The scheduling between LT and feeder bus may enhance the number of the public transport ridership, the viability of LRT and feeder bus, and provide optimal accessibility to LRT stations. The integration between LRT and feeder bus makes the passengers easier to move from origin to other places and reduce the waiting time where the services are on time. It will encourage people to use the public transport and it is hoped that public transport will be a preferable way for commuters to move in city centre. Public transport such as buses and trains or LRT are necessary in order to have better traffic flow. Furthermore, public transports is able to help in reducing the number of vehicles on the road and directly decreased congestion, accidents, delays and many other factors that may lead to congestion.